2022
DOI: 10.1136/bmjopen-2021-059046
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in patients with COVID-19 in the intensive care unit: evaluation of risk factors and mortality in a national cohort

Abstract: ObjectivesAcute kidney injury (AKI) is a frequent complication among critical ill patients with COVID-19, but the actual incidence is unknown as AKI-incidence varies from 25% to 89% in intensive care unit (ICU) populations. We aimed to describe the prevalence and risk factors of AKI in patients with COVID-19 admitted to ICU in Norway.DesignNation-wide observational study with data sampled from the Norwegian Intensive Care and Pandemic Registry (NIPaR) for the period between 10 March until 31 December 2020.Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
3
8
1
Order By: Relevance
“…High mortality of critically ill COVID-19 patients with advanced AKI or the need for RRT was also found in other studies. RRT was used in 10-31% of patients, with an ICU mortality of patients requiring RRT of 50-70% [ 14 , 27–29 ], which is comparable with our results. Numerous studies have also shown the association between AKI on ICU admission and mortality in critically ill COVID-19 patients [ 14–19 ], although they differed substantially in the patient population included and in the outcome.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…High mortality of critically ill COVID-19 patients with advanced AKI or the need for RRT was also found in other studies. RRT was used in 10-31% of patients, with an ICU mortality of patients requiring RRT of 50-70% [ 14 , 27–29 ], which is comparable with our results. Numerous studies have also shown the association between AKI on ICU admission and mortality in critically ill COVID-19 patients [ 14–19 ], although they differed substantially in the patient population included and in the outcome.…”
Section: Discussionsupporting
confidence: 88%
“…RRT was used in 10-31% of patients, with an ICU mortality of patients requiring RRT of 50-70% [ 14 , 27–29 ], which is comparable with our results. Numerous studies have also shown the association between AKI on ICU admission and mortality in critically ill COVID-19 patients [ 14–19 ], although they differed substantially in the patient population included and in the outcome. For instance, 90-day mortality in patients without AKI on admission was reported to be 7–15% versus 44% in our study, but only 70-81% of that study’s patients were ventilated, compared with the 100% in our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Age, acute circulatory failure during admission to hospital and AKI during admission to ICU were reported as determinants of both 30-day and 90-day mortality. [16] In systematic review and meta-analysis of 54 studies, AKI occurred in about 30% of the patients who were hospitalized with COVID-19, the course of >45% of patients who needed intensive care became complicated and 1 out of 5 patients who were admitted to the intensive care unit received kidney replacement therapy. [17] In a study by Fisher et al, the incidence of acute kidney injury was compared in patients who were hospitalized with COVID-19 and without COVID-19 and the incidence of acute kidney injury was found higher in COVID-19 patients compared to the control group (56.9% vs. 25.1% respectively).…”
Section: Discussionmentioning
confidence: 99%